PERENCANAAN PERPANJANGAN LANDAS PACU BANDAR UDARA MARATUA DENGAN PESAWAT ATR 72 - SAPUTRA, SANDY (KURVA S JURNAL MAHASISWA, 2017)
Sandy Saputra,The Runway is a rectangular area used by aircraft for landing and take-off at airports, having a